Measuring Halal City Index in Indonesia - Rengganis, Diaz Ayu (Maliki Islamic Economics Journal, 2024)
This study aims to measure the Halal City Index across Indonesian provinces using four key dimensions from the Global Muslim Travel Index (GMTI): Access, Communication, Environment, and Services (ACES). The research uses a qualitative approach through document analysis and expert judgment from Islamic economics lecturers. Secondary data from literature and documentation were analyzed using the Multi-Stage Weighted Index (MSWI) method. Results indicate that West Nusa Tenggara ranks highest in the Halal City Index, followed by Aceh and East Java—supported by strong infrastructure, halal services, and effective tourism promotion. In contrast, regions like Papua Mountains and South Papua score lowest due to limited facilities and infrastructure. These findings highlight the importance of enhancing infrastructure, services, and promotion to strengthen Muslim-friendly tourism development in Indonesia.